Profile Analysis of Self Efficacy in Grade 11 Students - Darma Gusti Lestari; Jaslin Ikhsan (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study was to determine the self-efficacy profile of Class XI IPA on colloidal material. This research is a descriptive type with a quantitative approach. The data analysis technique in this research is descriptive data analysis. Descriptive analysis was carried out on student self-efficacy questionnaire data after applying the project-based learning model so that the ideal average (Mi) and ideal standard deviation (Sdi) on self-efficacy data. This research was conducted at SMAN 2 South Bengkulu. This research was conducted in the even semester from May to June 2023. The research sample was the entire XI MIPA class of SMA Negeri 2 Bengkulu Selatan which amounted to 131 students. The results of this study indicate that the self-efficacy profile of students in PjBL is dominated by the high and medium categories with a percentage of 31% each. The self-efficacy of students in the PjBL model is dominated by the strength aspect of 41.42%, then the level aspect of 33.33%, and the generality aspect of 25.25%. The indicator of self-efficacy that has the highest score is the belief in being able to solve chemical problems/tasks in various levels of difficulty of 628.